2005
DOI: 10.1055/s-2005-861285
|View full text |Cite
|
Sign up to set email alerts
|

Techniques Using the Hemoglobin Index of the Gastric Mucosa

Abstract: ObjectivesColor changes seen at endoscopy are important for gastrointesti− nal endoscopic diagnosis. Quantification of the color information is useful for a scientific assessment of endoscopic color images. Since hemoglobin is the predominant pigment in the gastroin− testinal mucosa, measurement of the hemoglobin content is a reasonable method for quantifying the color in gastrointestinal endoscopic images. Recently, Tsuji et al. have developed a tech− nique for measuring mucosal hemoglobin content using elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 10 publications
0
13
0
1
Order By: Relevance
“…This quantitative assessment has rarely been applied to the diagnosis of gastric cancer (4)(5)(6)(7). If the color changes that are seen endoscopically in intramucosal gastric carcinomas are actually derived from the mucosal vascularity of the carcinomatous tissue, then it could be assumed that the measurement of the mucosal hemoglobin content would be a useful marker for a quantitative assessment of the endoscopic color of gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…This quantitative assessment has rarely been applied to the diagnosis of gastric cancer (4)(5)(6)(7). If the color changes that are seen endoscopically in intramucosal gastric carcinomas are actually derived from the mucosal vascularity of the carcinomatous tissue, then it could be assumed that the measurement of the mucosal hemoglobin content would be a useful marker for a quantitative assessment of the endoscopic color of gastric carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…Digitale Rekonstruktionen von Video-Endoskopbildern ermöglichen die Bildbearbeitung [22]. Der Hämoglobingehalt in der Mukosa (der Hä-moglobin-Index) kann anhand der Farbe des reflektierten Lichts beurteilt werden [11,24,26]. Die neue Technik des Narrow-Band Imaging (NBI) kombiniert das Potenzial der Vergrößerungsendo-skopie mit dem der Bildbearbeitung [5 -7].…”
Section: Klinische Grundlagenunclassified
“…Applying an absolute value of the IHb, the detection of H. pylori infection in the stomach has been validated with high diagnostic sensitivity and specificity [18][19][20][21]. Besides differentiating benign from malignant gastric lesions [17,22,23], the IHb modality can correlate well with the severity of gastric mucosal inflammations, oxidative stress, and even levels of cytokines such as IL-8 [21,23]. In addition to its application in the stomach, several studies have suggested that the application of IHb modality can improve the detection of colon neoplastic lesions [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%